Peran Pengelola Wisata Religi Al-Qur’an Al-Akbar Dalam Pengembangan Dakwah Berkelanjutan Di Kota Palembang - Dita Riya; Nurseri Hasnah Nasution; Muslimin . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the role of the management of the Al-Qur’an Al-Akbar religious tourism site in developing sustainable da’wah in Palembang City. The background of this research is based on the importance of optimizing religious tourism as a medium of da’wah that is not only temporary but also sustainable and impactful in enhancing the community’s religious understanding. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the management plays a strategic role in developing da’wah through educational programs, dissemination of Islamic values, and the utilization of tourism as a medium for religious learning. The da’wah activities are not only informative but also educational and persuasive, attracting visitors from diverse backgrounds. Furthermore, the sustainability of da’wah is supported by program innovation, media utilization, and collaboration with various stakeholders. However, there are still challenges such as limited facilities, human resources, and suboptimal promotion. Therefore, the Al-Qur’an Al-Akbar religious tourism site has great potential as a medium for sustainable da’wah that not only strengthens Islamic values but also supports the development of religious tourism in Palembang City.